Europe forever? Czech political parties on the orientation of Czech foreign policy. Issue 4 (2nd October 2021) - Hloušek, Vít; Kaniok, Petr
ABSTRACT: The foreign policy orientation of Central and Eastern European (CEE) countries has been changing in recent years. Countries which were, since the 1990s, oriented towards structures such as NATO or EU have started to flirt with partners such as Russia and China. Apart from Russian and Chinese interventions into CEE domestic development, little is known on whta can explain these changes. Our article fills this gap by analysing the foreign policy approaches of Czech political parties. We argue that European Internationalism is the preferred direction of Czech political parties. However, changes in the Czech party system and multiple EU crises signal contestation of this direction and a possible turn to the East.